Relationship between triglyceride levels and different snoring states: a systematic review and meta-analysis - Fei-Fei Hou; Bei-Bei Wang; Ye Chen; Qiong Wang; Qiong Wu; Li-Na Yan (European Journal of Medical Research)
Abstract Objective High triglyceride (TG) levels are important risk factors for cardiovascular disease (CVD). Some recent studies have shown that snoring is also closely related to elevated TG levels. The specific pathogenesis of elevated TG levels in snoring patients is still unclear. Therefore, we performed this meta-analysis to evaluate the relationship between snoring and elevated TG levels. Materials and methods A systematic search was conducted in four online electronic databases as of Jul 1, 2024. The standardized mean difference (SMD) and corresponding 95% confidence interval (CI) for TG levels in each study were pooled. Moreover, we performed subgroup analysis according to snoring status and body mass index (BMI). All the data were pooled and analysed with Review Manager 5.3. Results The meta-analysis included five studies with 39,102 participants. Our results revealed that snoring was associated with elevated TG levels, with a pooled SMD of 0.23 (95% CI 0.14 to0.32; P < 0.00001). We found that occasional snoring and habitual snoring were associated with high TG levels, with pooled SMD of 0.26 (95% CI 0.04to0.49; P = 0.002) and 0.29 (95% CI 0.16to0.43; P < 0.0001), respectively. According to the subgroup analysis of BMI, BMI < 25 kg/m2 and BMI ≥ 25 kg/m2 were associated with increased TG levels, with pooled SMD of 0.13 (95% CI 0.04 to 0.22; P = 0.004) and 0.24 (95% CI 0.10 to 0.39; P = 0.0007), respectively. Conclusions Our meta-analysis revealed that both occasional and habitual snoring were associated with elevated TG levels. More importantly, our findings also revealed that the relationship between snoring-induced elevated TG levels and BMI was fragile.